Association Between Personal and Environmental Factors, Body Position on Low Back Pain at Dr. Moewardi Hospital, in Surakarta - Rina Kurnia; Rita Benya Adriani (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Low Back Pain or LBP often encountered in daily practice, especially in industrialized countries. The study showed that 90.9% of LBP patients experienced a relapse more than once in a year, the relapse was triggered by personal factor, work environment and lack of health information. The purpose of this study was to analyze factors associated with recurrence prevention in patients with Low Back Pain at Medical Rehabilitation Instalation Dr. Moewardi Surakarta HospitalSubjects and Method: The study was an observational analytic study with cross sectional design. A total of 60 patients with LBP. That data was collected with a questionairre and analyzed by using multiple logistic regression.Results: There was a positive correlation between personal factors and recurrence prevention in Low Back Pain: there was a correlation between age and recurrence prevention in Low Back Pain but it was not statistically significant (O =2.09; 95% CI= 0.36 to 12.09 ; p=0.412), there was a correlation between sex and recurrence prevention in Low Back Pain but it was not statistically significant (OR=1.52; 95% CI=0.08 to 28.78; p=0.781), there was a correlation between education level and recurrence prevention in Low Back Pain but it was not statistically significant (OR=2.38; 95% CI=0.41 to 14.05; p=0.337), there was a correlation between employment and recurrence prevention in Low Back Pain and it was statistically significant ( OR=9.16; 95% CI=1.35 to 62.39; p = 0.024), there was a correlation between perceptions of Low Back Pain and recurrence prevention in Low Back Pain and it was statistically significant (OR=27.81; CI=95% 2.14 to 361.33; p=0.011). There was a positive correlation between environmental factors and recurrence prevention in Low Back Pain: there was a correlation between accessibility to health service and recurrence prevention in Low Back Pain but it was not statistically significant (OR=0.49; 95% CI=0.02 to 14.81; p=0.684), there was a correlation between environment accessibility and recurrence prevention in Low Back Pain but it was not statistically significant (OR=0.73; 95% CI=0.04 to 14.22; p=0.834), there was correlation between family support and recurrence prevention in Low Back Pain and it was not statistically significant (OR=0.30; 95% CI=0.02 to 5.50; p=0.303) .There was a positive correlation between education on Proper Body Mechanics with recurrence prevention in Low Back Pain and it was statistically significant (OR=35.33; 95% CI=1.65 to 757.32; p=0.023). The most dominant variable in LBP recurrence prevention was patients perceptions of Low Back Pain (p= 0.011).Conclusion: Employment, perceptions of Low Back Pain, and education on proper body mechanic were variables was statistically significant for LBP relaps prevention in this study.Keywords: personal factors, environmental factors, education on proper body mechanics, relapse prevention, LBPCorrespondence: Rina Kurnia. Health Polytechnic, Poltekkes Kemenkes Surakarta University, Surakarta.Journal of Health Promotion and Behavior (2016), 1 (1): 19-25https://doi.org/10.26911/thejhpb.2016.01.01.03